Perioperative nursing of a centenarian with intertrochanteric fracture undergoing PFBN internal fixation (1例百岁老人粗隆间骨折行微创新型仿生髓内钉内固定的围手术期护理) - FAN Lingling (樊玲玲); WANG Huizheng (王慧征) (Journal of International Translational Medicine Limited, 2023)
This paper summarizes the perioperative nursing experience of a centenarian patient with intertrochanteric fracture of femur undergoing Proximal Femoral Bionic Nail(PFBN) internal fixation. The mind mapping mission mode was adopted, and patient was given comfortable nursing intervention. Based on Traditional Chinese Medicine therapy, tapping therapy and massage were carried out to ensure patient comfort. Moreover, standardized thrombotic prevention measures, enhanced recovery after surgery, personalized functional exercise path, and progressive rehabilitation training were carried out to reduce the risk of perioperative deep vein thrombosis free and improve the early functional recovery. (本文总结1例百岁老人股骨粗隆间骨折行新型仿生髓内钉内固定的围手术期护理经验。采用思维导图宣教模式, 给予患者舒适护理干预, 开展中医养生护理, 采用敲打、按摩的方式提升患者舒适度; 制定规范的血栓预防措施, 运用加速康复外科理念、个性化功能锻炼路径、递进式康复训练, 降低患者围术期深静脉血栓发生风险, 促进早期功能恢复。)